Baccalaureate nursing education institutions' key performance indicators: a review of the existing indicators and qualitative analysis of expert interviews - Marjan Ghofrani; Leila Valizadeh; Vahid Zamanzadeh; Akram Ghahramanian; Ali Janati; Fariba Taleghani (BMC, 2023)
Abstract Background Improvements in nurses' and midwives' education will increase workforce quantity and quality. Continual improvement of organization performance is based on continual measuring; Appropriate indicators must be selected to measure and appraise the performances. This study aimed to recognize and categorize key performance indicators (KPIs) for baccalaureate nursing education institutions' performance measurement. Methods This study had two phases: (1) Interview: Seven semi-structured interviews were conducted with faculty members and nurses. (2) Narrative Literature review: schools' and universities' reports and web pages were assessed to recognize KPIs. The data analysis method was directed content analysis. The Donabedian Model components were used to guide the data analysis. Results The total number of indicators retrieved was 468; 75 were from interviews with faculty members and nurses and 393 were from the literature review. Indicators were categorized into: Structure (staff; equipment, resources, and facilities; guidelines), Process (education; communication and collaboration; evaluation), and Outcome (survey and accreditation; national and international recognition; satisfaction; sustainability and financial efficiency; students; alumni; knowledge related to the field). Conclusions A number of indicators were identified that were categorized into various groups related to the performance of nursing schools. Further investigations are needed with different groups of stakeholders including students, professional associations, healthcare institutions, alumni, and clients. As well in some areas, new or composite indicators may need to be developed. Also, each institution needs to select appropriate indicators based on its context, policy goals, and infrastructure.